(27-32)/9*2
-5/9*2
-0.9*2
-1.1 or C. 1
Answer:
The expressions which equivalent to
are:
⇒ B
⇒ C
Step-by-step explanation:
Let us revise some rules of exponent
Now let us find the equivalent expressions of 
A.
∵ 4 = 2 × 2
∴ 4 = 
∴
=
- By using the second rule above multiply 2 and (n + 2)
∵ 2(n + 2) = 2n + 4
∴
=
B.
∵ 4 = 2 × 2
∴ 4 = 2²
∴
= 2² ×
- By using the first rule rule add the exponents of 2
∵ 2 + n + 1 = n + 3
∴
=
C.
∵ 8 = 2 × 2 × 2
∴ 8 = 2³
∴
= 2³ ×
- By using the first rule rule add the exponents of 2
∵ 3 + n = n + 3
∴
=
D.
∵ 16 = 2 × 2 × 2 × 2
∴ 16 = 
∴
=
×
- By using the first rule rule add the exponents of 2
∵ 4 + n = n + 4
∴
=
E.
is in its simplest form
The expressions which equivalent to
are:
⇒ B
⇒ C
Where is the persons info
Answer:
he has 11 dimes and 15 nickels
Step-by-step explanation:
i kept going down reducing the amount of dimes and adding to the amount of nickels and found that 11 dimes is $1.10 and 15 nickels is $0.75
???????????????????????????????????